1997
DOI: 10.1074/jbc.272.35.21977
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Characterization of Inosine 5′-Monophosphate Dehydrogenase from Borrelia burgdorferi

Abstract: Inosine 5-monophosphate dehydrogenase (IMPDH) is the rate-limiting enzyme in de novo guanine nucleotide biosynthesis. IMPDH converts IMP to xanthosine 5-monophosphate with concomitant conversion of NAD ؉ to NADH. All IMPDHs characterized to date contain a 130-residue "subdomain" that extends from an N-terminal loop of the ␣/␤ barrel domain. Inosine 5Ј-monophosphate dehydrogenase catalyzes the conversion of IMP to XMP 1 with the concomitant reduction of NAD to NADH. This reaction is the rate-limiting step in gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 32 publications
4
63
0
Order By: Relevance
“…1). Moreover, it has been demonstrated that the GuaB and GuaA enzymes, the final two enzymes in the B. burgdorferi purine salvage pathway required for guanine nucleotide synthesis (28,67), are able to use dIMP and dXMP, respectively, as substrates to produce dGMP (23), in addition to the well-characterized substrates IMP and XMP, respectively, to generate GMP (28,67) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Moreover, it has been demonstrated that the GuaB and GuaA enzymes, the final two enzymes in the B. burgdorferi purine salvage pathway required for guanine nucleotide synthesis (28,67), are able to use dIMP and dXMP, respectively, as substrates to produce dGMP (23), in addition to the well-characterized substrates IMP and XMP, respectively, to generate GMP (28,67) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The enzymes required for the final two steps of guanine nucleotide biosynthesis, IMPDH and GMP synthase, are encoded by the guaB and guaA genes, respectively. The guaA and guaB genes and the corresponding activities of their protein products are conserved in B. burgdorferi (28,67). These genes are typically carried on the chromosomes of bacterial species.…”
mentioning
confidence: 99%
“…Monovalent cations, such as K + , activate IMPDH (Hedstrom, 2009;Kerr et al, 2000;Zhou et al, 1997) and in a similar fashion Mt-GuaB2 exhibited a requirement for KCl (Fig. 3a).…”
Section: Biochemical Properties Of Recombinant Mt-guab Orthologuesmentioning
confidence: 99%
“…Proposed or known functions have also been determined for chbC (50), oppAIV (7), and guaB (30,51,53) (Fig. 1), all of which have been successfully inactivated without inhibition of in vitro growth.…”
Section: Discussionmentioning
confidence: 99%